PENERAPAN METODE DECISION TREE UNTUK REKOMENDASI TUJUAN POLI PADA RUMAH SAKIT UMUM DAERAH BAJAWA - Sandrianus Rewo Ngeo; Latipah (Antivirus : Jurnal Ilmiah Teknik Informatika, 2021)
The increase in population in Indonesia has contributed to increasing public awareness and demands for the quality of health services. In terms of the level of awareness of health, this can increase the number of hospital visitors who experience health problems. With the rapid development of technology, it is hoped that it can overcome health problems. One of the problems that often occur in the health sector is the lack of medical personnel, specialist doctors, and also technology to facilitate health services. This causes the patient is often referred only to a general practitioner, without considering the description of the disease that has been suffered. This study aims to overcome this problem by implementing a decision tree based poly destination recommendation system to provide recommendations for poly destination s to patients visiting the Bajawa Regional General Hospital. The poly destination recommendation system is a decision support system that can take decisions to help provide recommendations for poly destination s that are in accordance with the patient's disease description and history. In this study, it has 3 attributes as input, namely: time to visit, description of disease, and type of care, while the output is the name of the poly unit as the target of the decision. This study aims to assist the Bajawa Regional General Hospital in recommending poly destination s according to existing data on patients who have previously been given to the administration section of the Bajawa Regional General Hospital. The results showed that the expert system program and the decision tree in the recommendation system application had succeeded in providing recommendations for poly destination s according to the information on the patient's disease at the Bajawa Regional General Hospital.